Developing a Prototype for Enhancing Data Security in LoRaBased Theft Detection Systems Using ASCON-128 Encryption - Amelia, Fetty; Wulandari Hartejo, Bella (IAES Indonesian Section, 2025)
Asset protection is crucial for organizations to prevent theft. This study presents a LoRa-based theft detection prototype enhanced with ASCON-128 encryption for secure data transmission. The system consists of a transmitter attached to assets and a receiver in a monitoring room, featuring a web-based digital map for real-time tracking. ASCON-128, a NIST-standard lightweight encryption algorithm, ensures data confidentiality and integrity against ManIn-The-Middle (MITM) attacks. The system was evaluated based on transmission speed, power consumption, and security performance. Results indicate that ASCON-128 integration reduces data transmission speed by 42.7% in Line-of-Sight (LOS) and 45.35% in Non-Line-of-Sight (NLOS) conditions. Power consumption increased by 2.7% in standby mode and 12.85% under simulated attack scenarios. Despite these trade-offs, encryption provides significant security benefits with acceptable resource overhead, making it a viable solution for LoRa-based asset tracking and theft detection.